2014
DOI: 10.1016/j.bbagen.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification, modeling and ligand affinity of early deuterostome CYP51s, and functional characterization of recombinant zebrafish sterol 14α-demethylase

Abstract: Background Sterol 14α-demethylase (cytochrome P450 51, CYP51, P45014DM) is a microsomal enzyme that in eukaryotes catalyzes formation of sterols essential for cell membrane function and as precursors in biosynthesis of steroid hormones. Functional properties of CYP51s are unknown in non-mammalian deuterostomes. Methods PCR-cloning and sequencing and computational analyses (homology modeling and docking) addressed CYP51 in zebrafish Danio rerio, the reef fish sergeant major Abudefduf saxatilis, and the sea ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…Interestingly, despite the lack of clear steroidogenic CYP orthologs in tunicates, several ovarian steroids have been identified in Ciona intestinalis (Cangialosi et al, 2010). However, as we recently noted, there is no lanosterol 14-a demethylase (CYP51) in either of the Ciona species’ genomes (Morrison et al, 2014). CYP51 is required for de novo cholesterol synthesis leading to an obligate dietary or commensal source for steroid precursors in Ciona spp.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Interestingly, despite the lack of clear steroidogenic CYP orthologs in tunicates, several ovarian steroids have been identified in Ciona intestinalis (Cangialosi et al, 2010). However, as we recently noted, there is no lanosterol 14-a demethylase (CYP51) in either of the Ciona species’ genomes (Morrison et al, 2014). CYP51 is required for de novo cholesterol synthesis leading to an obligate dietary or commensal source for steroid precursors in Ciona spp.…”
Section: Discussionmentioning
confidence: 82%
“…In fact, the genomes of the ascidian tunicate species Ciona intestinalis and Ciona savignyi lack CYP51 (lanosterol demethylase), the enzyme required for the biosynthesis of the steroid precursor cholesterol (Morrison et al, 2014). CYP51 also appears to be missing from the genomes of the appendicularian Oikopleura dioica and the molgulid Molgula occidentalis , suggesting that CYP51 was lost early in tunicate evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Morrison et al (2014) found that ketoconazole has the potential to inhibit zebrafish CYP51, based on the results of a docking experiment. Skolness et al (2013) demonstrated that propiconazole could inhibit steroidogenesis in the fathead minnow (Pimephales promelas) and down-regulated the expression of some key genes, such as CYP51, HMGCR and FDPS, in the hepatic synthesis process.…”
Section: Discussionmentioning
confidence: 99%
“…Selective inhibition of the enzyme would cause depletion of ergosterol and accumulation of lanosterol and result in the growth inhibition of the fungal cell [1].In this study, a series of benzimidazole derivatives containing a triazole ring that are structurally related to the famous antifungal azole pharmacophore were synthesized and their structures were characterized by spectral (IR, 1 H-NMR, 13 C-NMR, and MS spectra) analyses. Compounds 5i and 5s showed the most promising antifungal activity with a MIC50 value of 0.39 ug/mL against Candida species.…”
mentioning
confidence: 99%
“…Selective inhibition of the enzyme would cause depletion of ergosterol and accumulation of lanosterol and result in the growth inhibition of the fungal cell [1].…”
mentioning
confidence: 99%